2023
DOI: 10.1002/ijgo.14537
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy as an opportunity to prevent type 2 diabetes mellitus: FIGO Best Practice Advice

Abstract: Gestational diabetes (GDM) impacts approximately 17 million pregnancies worldwide. Women with a history of GDM have an 8–10‐fold higher risk of developing type 2 diabetes and a 2‐fold higher risk of developing cardiovascular disease (CVD) compared with women without prior GDM. Although it is possible to prevent and/or delay progression of GDM to type 2 diabetes, this is not widely undertaken. Considering the increasing global rates of type 2 diabetes and CVD in women, it is essential to utilize pregnancy as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…30 Despite this, considerable work is still required to establish follow-up for women following pregnancy with gestational diabetes, to ameliorate the risks of type 2 diabetes. 31 FIGO is committed to improve women's health across the life course and the FIGO Committee on Impact of Pregnancy on Longterm Health will continue to advocate for improved women's health by:…”
Section: Many Healthcare Systems Have Robust Neonatal and Child Follo...mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Despite this, considerable work is still required to establish follow-up for women following pregnancy with gestational diabetes, to ameliorate the risks of type 2 diabetes. 31 FIGO is committed to improve women's health across the life course and the FIGO Committee on Impact of Pregnancy on Longterm Health will continue to advocate for improved women's health by:…”
Section: Many Healthcare Systems Have Robust Neonatal and Child Follo...mentioning
confidence: 99%
“…To date, lifestyle and pharmacological interventions have been shown to reduce the risk of later type 2 diabetes 30 . Despite this, considerable work is still required to establish follow‐up for women following pregnancy with gestational diabetes, to ameliorate the risks of type 2 diabetes 31 …”
mentioning
confidence: 99%
“…Despite several professional bodies recommending postpartum assessment and interventions to reduce the risk of long‐term health complications, 1,2,15 maternal compliance with follow‐up appointments remains low. A study indicated that only half of the high‐risk women attended postpartum check‐ups 16 .…”
Section: Figurementioning
confidence: 99%
“…Accurate prediction of incident GDM may enable prevention. FIGO Best Practice Advice recommends viewing pregnancy as an opportunity to prevent type 2 diabetes mellitus Adam et al (2023).…”
Section: Introductionmentioning
confidence: 99%